2018
DOI: 10.1002/lom3.10242
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative real‐time polymerase chain reaction (PCR) and droplet digital PCR duplex assays for detecting Zostera marina DNA in coastal sediments

Abstract: The sequestration of atmospheric CO 2 in seagrass meadows as organic carbon (OC) has been attracting more attention as a means for climate change mitigation and adaptation. A direct method to detect seagrass DNA in coastal sediments, which is essential to unravel long-term seagrass-derived OC accumulation, was developed based on environmental DNA (eDNA) detection techniques. Quantitative real-time polymerase chain reaction (qPCR) and droplet digital PCR (ddPCR) were applied to quantify Zostera marina DNA in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 66 publications
2
24
1
Order By: Relevance
“…It is commonly reported that ddPCR overcomes the challenges connected to inhibitory substances to a higher extent than qPCR, and displays both higher sensitivity and higher quantification accuracy (Dingle et al, 2013;Rački et al, 2014;Zhao et al, 2016), and several studies have highlighted the benefits of ddPCR for eDNA detection (e.g., Doi et al, 2015a;Hunter et al, 2017;Hamaguchi et al, 2018;Mauvisseau et al, 2019a;Brys et al, 2020). However, while ddPCR offers absolute quantification, the variation in estimated copy numbers increases at low numbers, therefore the LOQ of ddPCR is often within the same range as LOQ for qPCR (Dobnik et al, 2015).…”
Section: Efficiency For Edna Detection Of Noble Crayfish -Qpcr Versusmentioning
confidence: 99%
“…It is commonly reported that ddPCR overcomes the challenges connected to inhibitory substances to a higher extent than qPCR, and displays both higher sensitivity and higher quantification accuracy (Dingle et al, 2013;Rački et al, 2014;Zhao et al, 2016), and several studies have highlighted the benefits of ddPCR for eDNA detection (e.g., Doi et al, 2015a;Hunter et al, 2017;Hamaguchi et al, 2018;Mauvisseau et al, 2019a;Brys et al, 2020). However, while ddPCR offers absolute quantification, the variation in estimated copy numbers increases at low numbers, therefore the LOQ of ddPCR is often within the same range as LOQ for qPCR (Dobnik et al, 2015).…”
Section: Efficiency For Edna Detection Of Noble Crayfish -Qpcr Versusmentioning
confidence: 99%
“…Droplet digital PCR (ddPCR) confirmed ribavirin, harringtonine, and 2-hydroxytetradecanoic acid (2-HOM) were effective at inhibiting SGIV infection [ 94 ]. In addition, ddPCR was also considered more suitable for the detection of Z. marina DNA from marine sediments [ 95 ].…”
Section: Other Methods Used With Dna Barcodingmentioning
confidence: 99%
“…In the marine environment, eDNA has been used primarily to detect microbes and viruses, eukaryotic phytoplankton, zooplankton, macro-invertebrates, and vertebrates (Djurhuus et al, 2018;Goodwin et al, 2019). But eDNA has also been used to confirm the historic presence of seagrass at locations where it no longer exists (Hamaguchi et al, 2018). The only other study using eDNA from marine plants of which we are aware estimated the contribution of seagrasses and macroalgae to carbon stocks in sediments (Reef et al, 2017).…”
Section: Opportunities and Emerging Technologiesmentioning
confidence: 99%